Linking long-term patterns of landscape heterogeneity to changing ecosystem processes in the Kruger National Park, South Africa - MacFadyen, Sandra (Stellenbosch : Stellenbosch University, 2018)
Thesis (PhDAgric)--Stellenbosch University, 2018.